Fujifilm X-T3 : pocket guide : buttons, dials, settings, modes, and shooting tips. (Rocky Nook, 2023)
Designed for photographers who haven't memorized every button, dial, setting, and feature on their Fujifilm X-T3, Rocky Nook's handy and ultra-portable quick reference Pocket Guide helps you get the shot when you're out and about. This camera guide helps you: Confirm that your camera is set up properly with the pre-shoot checklist Identify every button and dial on your camera Learn the essential modes and settings you need to know Dive deeper with additional features of your camera Execute step-by-step instructions for shooting multiple exposures, in-camera HDR, time-lapse movies, and more Follow tips and techniques for getting great shots in typical scenarios (portrait, landscape, freezing action, low light, etc.) Put your Fujifilm X-T3 to use today with this essential reference.